A Bone Marrow Aspirate and Trephine Simulator. Issue 4 (August 2015) - Yap, Eng Soo; Koh, Pei Lin; Ng, Chin Hin; de Mel, Sanjay; Chee, Yen Lin
Abstract : Introduction: Bone marrow aspirate and trephine (BMAT) biopsy is a commonly performed procedure in hematology-oncology practice. Although complications are uncommon, they can cause significant morbidity and mortality. Simulation models are an excellent tool to teach novice doctors basic procedural skills before performing the actual procedure on patients to improve patient safety and well-being. Methods: There are no commercial BMAT simulators, and this technical report describes the rationale, technical specifications, and construction of a low-cost, easily constructed, reusable BMAT simulator that reproduced the tactile properties of tissue layers for use as a teaching tool in our resident BMAT simulation course. Preliminary data of learner responses to the simulator were also collected. Results: From April 2013 to November 2013, 32 internal medicine residents underwent the BMAT simulation course. Eighteen (56%) completed the online survey, 11 residents with previous experience doing BMAT and 7 without experience. Despite the difference in operative experience, both experienced and novice residents all agreed or strongly agreed that the model aided their understanding of the BMAT procedure. All agreed or strongly agreed that this enhanced their knowledge of anatomy and 16 residents (89%) agreed or strongly agreed that this model was a realistic simulator. Conclusions: We present a novel, low-cost, easily constructed, realistic BMAT simulator for training novice doctors to perform BMAT.